THE QUALITATIVE SYSTEMIC ANALYSIS IN THE CONTEXT OF QUALITATIVE RESEARCH METHODS - Rolando, Lalanda-Gonçalves (European Scientific Journal, ESJ, 2015)
Alex Mucchielli in the University of Montpellier developed the qualitative systemic analysis. In this communication, we intend to present the principles of this methodological approach in human and social sciences. We believe that this qualitative approach is innovative in the context of qualitative methods and allows a new perspective in the analysis of the communication processes in social organizations. The main operations of the systemic qualitative method are the iterative definition of the framework, the identification of the recurrences and circular causalities, and the modeling of relations/social exchanges. These operations aim to find the sense/meaning of a social exchange system. The logic of the system, found by an approach that respects all the validation process in the qualitative methods, is important to clarify the specificity of the research in human and social sciences. In fact, qualitative research is one of the scientific achievements that are most relevant in the comprehension of the dynamics of human interaction.